Climate change and trends of the rainfall of the city of Recife (Research, Society and Development, 2020)
Subject of major discussions, recent climate changes show the impact and magnitude of anthropic actions in the natural environment. The magnitude of the impacts caused by the changes reflects not only the major disasters caused by extreme events, but also the economic and social spheres, as these changes trigger an imbalance in ecosystems, as well as in climate configuration and hydrological regimes. Therefore, this study aims to analyze the transformations of rainfall over time by detecting trends in time series of hydrological data. The trends and fluctuations of the climatological variables, referring to the precipitation series obtained from 4 rainfall seasons located in Recife-PE, were analyzed by the Mann-Kendall test. According to the Mann-Kendall sequential test, there was a period of significant increase in rainfall that may have its occurrence related to extreme events in the region. Thus the results express a non-significant reduction in rainfall patterns in Recife.